ANALISIS RISIKO KESELAMATAN KERJA PADA BAGIAN PRODUKSI DENGAN METODE JOB SAFETY ANALYSIS DAN HAZARD AND OPERABILITY STUDY - Aldora Gavrila Faiq; Ayudyah Eka Apsari (JURNAL ILMIAH NUSANTARA, 2024)
. CV Tunas Karya produces a variety of industrial machinery. This business may be found in Yogyakarta City's Jalan Kaliurang Dsn. Beji, Harjo Binangun, Pakem, Sleman District. The purpose of this study is to determine the risk of workplace accidents in CV. Tunas Karya's production process. The measurement of the effort taken to prevent such mishaps and the amount of risk that accidents would occur throughout the production process are the other goals. The Hazard and Operability Study Method is an engineering technique to find and reduce hazards employed in industrial processes, while the Job Safety Analysis Method seeks to examine current hazards. After using the Job Safety Analysis and Hazard and Operability Study methods to process data on occupational accident risk, the job accident risk ratio was found with a 47% moderate risk category and a 53% low risk category. To prevent the occurrence of potential hazards, the plan recommends the provision of first aid equipment located in the factory and the use of APDs that meet K3 standards.